Pengaruh Pemberian Ekstrak Etanol Umbi Mahakaan terhadap Waktu Perdarahan dan Pembekuan serta Jumlah Trombosit Darah Mencit Putih Betina - Dharma, Surya; Dachriyanus, .; Sartika, Zikra (Indonesian Research Gateway)
The effect of aethanolic extract of mahakaan's (Gynura pseudochina (L) DC tuber on shortening bleeding and coagulation time and trombocytes cell of the white female mice has been studied. The overal doses used were 30,100 and 300 mg/kg BW. The effect was observed on 1st, 7th, 14th and 21st days by using the modified cutting tail method, slide method and using hemositometer. As a comparator used vitamin K with dose of 0,026 mg/20g BW was given. The result indicated that the extract has ability to shorten bleeding and coagulation time at all doses, and the dose of 300 mg/kg BW showed a stronger effect on shortening bleeding time compared to vitamin K 0,026 mg/20g BW (p<0,01). The doses of 100 and 300 mg/BW showed a stronger effect on shortening coagulation time. The thrombocytes was not influenced by the all doses, and neither was the lenght of the administration (p>0,01). keywords : Gynura pseudochina (L.) DC), bleeding time, coagulation time and level of thrombocyt.